Micronutrient Supplementation During Pregnancy, Birth Weight and Neonatal Mortality in Uganda: A Causal Mediation Analysis. (29th May 2020) - Ssentongo, Paddy; Ba, Djibril; Fronterre, Claudio; Ericson, Jessica; Gernand, Alison; Wang, Ming; Du, Ping; Liao, Duanping; Chinchilli, Vernon; Schiff, Steven
Abstract: Objectives: Low birth weight (LBW) is a significant risk factor for death in the first 30 days of life. Maternal iron-deficiency anemia during pregnancy increases the risk of LBW. We aimed to explore whether antenatal IFA supplementation reduces neonatal mortality in Uganda and to examine if the association of IFA supplementation with neonatal death is mediated through LBW. Methods: We used a retrospective birth cohort from the 2016 population-based Uganda demographic and health survey. We examined information on neonatal survival, sociodemographic and intake of IFA supplementation of 9203 women and 17, 202 live-born, term infants ≤ 5 y before the survey. Birth weight was categorized as very low (VLBW, defined as < 1500 g or very small baby as perceived by the mother), low (LBW, birth weight of < 2500 g or baby smaller than average as perceived by the mother), and normal (NBW, ≥ 2500 g or an average and larger baby as perceived by the mother). Causal mediation analysis (CMA) treating the birth weight as a mediator was conducted to measure the direct and indirect effects of IFA on neonatal mortality (death of a live-born infant during the first 30 d of life). Results: IFA supplementation was reported in 89% of women. The prevalence of LBW and VLBW was 21% and 7% respectively. 474 (3%) babies died within the 30 d after birth, 320 (66%) died within the first 24 h and 469 (99%) died within the first week of life (early neonatal mortality). IFA supplementation during pregnancy was independently associated with a 56% reduction in neonatal mortality [(hazard ratio (HR): 0.44; 95% CI 0.31, 0.61); P < 0.0001] and 26% reduction in VLBW (Relative risk (RR): 0.74; 95% CI 0.60, 0.92, P = 0.007). There was a linear dose-response relationship between the category of birth weight and increased neonatal mortality (LBW versus NBW: RR: 1.39 95% CI: 1.05–1.81, P = 0.02, VLBW versus NBW: RR; 3.6: 95% CI: 2.83–4.53, P < 0.0001). CMA showed that 6% of the effect of IFA supplement on reducing neonatal mortality was meditated through reducing the risk of VLBW but not through LBW, and 94% of the causal effect was direct. Conclusions: The use of antenatal iron/folic acid supplements during pregnancy is an important intervention to reduce neonatal mortality. These findings indicate that the association is weakly mediated through improved birth weight, and other mediators should be identified in future studies. Funding Sources: NIH.